Web-Based Weekly Cash Accounting Information System Design at XYZ Institution - Nur Amalia, Firdha Raissa; Karyadi, Karyadi; Yuliansyah, Dwi; Kusumadiarti, Rini Suwartika (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
This study aims to create a web-based accounting information system to assist user needs, especially the finance department in processing weekly cash financial data at XYZ company, as well as to produce reports needed by users more effectively and efficiently. This research method uses qualitative research methods. With the results of this system design it can be a solution for the future, especially for the finance section because it is able to help check data, because this system is made to be able to search data based on day, date, year or transaction number so that the process can be more time efficient.